Power dynamics and regional security in Latin America - Suárez, Marcial ; Villa, Rafael ; Weiffen, Brigitte (Palgrave Macmillan, 2020)
This volume explores the repercussions of a changing world order on regional security in Latin America. It examines how global and regional power shifts impact on the evolution of regional institutions as well as on state policies adopted in response to regional security challenges such as border conflicts, political instability, migration, drug-trafficking, organized crime, and terrorism. Contributions to this volume analyze the topic from three angles: power dynamics and its effects on regional security governance; the contribution of regional institutions to the management of security challenges; and the impact of power dynamics on states’ shifting security priorities. Written by specialists from Brazil, Argentina, Colombia, Mexico, the United States and Europe, the chapters weave theory and case studies to provide a rich description of the impact of power and politics on regional security in Latin America. This book is an invaluable resource for students, scholars and practitioners interested in Latin American politics, regional cooperation, and war and conflict studies, as well as international security and international relations in general.